Social awareness of women and sustainable development a field study on the governmental and private sectors of work in Diwaniyah Governorate - ثائر كاظم رحيم, د. (lark, 2021)
The study  is starts with a basic hypothesis that the development of the status of women and the elimination of gender gaps and the realization of the principle of equal opportunities are based on two main axes: the first are self-tools related to women themselves through their levels of awareness, conviction, abilities, potentials and desires that provide self-energy for the process. Participation,  and the creation and management of positive opportunities that vary according to these instruments. Conscious that the  parity environment in general and human development in particular study used the analysis and interpretation of the data contained in the Human Development Report for the Governors of Diwaniyah and the use of public opinion survey methodology. And, at any time, with clear objectives, a comprehensive strategy planned for all dimensions and elements of society, based on an accurate information base in understanding Problems and needs, setting goals and proposing alternatives, choosing the best ways to match the needs and potentials available, mobilizing efforts and coordinating roles, ensuring their complementarity and synergy, and reducing the possibility of conflict, through careful and continuous follow-up, and serious and continuous evaluation, to measure success levels, to sharpen energies and improve capacity And launch creations